Callimachus and the Etruscans: Human Sacrifice between Myth, History, and Historiography - Di Fazio, Massimiliano (Histos, 2013)
This paper assesses the historicity of a fragment of Callimachus which attests a human sacrifice by the Etruscans after a victory over the people of Lipari. It argues that the story is best seen as an example of the Greek tendency to represent the Etruscans as savage and contextualizes this tendency particularly within the attempts of the Deinomenid tyrants to represent themselves as defenders of Greek civilization against such barbarian savagery. Finally, it speculates on the ultimate literary or historiographical source of the story.